2010
DOI: 10.1007/s10096-009-0866-6
|View full text |Cite
|
Sign up to set email alerts
|

In vitro activities of doripenem and other carbapenems against clinically important bacteria isolated in intensive care units: nationwide data from the SMART Programme

Abstract: This nationwide surveillance of clinically important bacteria from the intensive care units (ICUs) of major teaching hospitals throughout Taiwan investigated the susceptibilities to doripenem and other comparator carbapenems from September through November 2005. Minimum inhibitory concentrations (MICs) were determined for 1,311 clinical isolates using the broth microdilution method according to Clinical and Laboratory Standards Institute (CLSI) 2005 guidelines. Doripenem showed similar (within four-fold differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 8 publications
0
8
2
Order By: Relevance
“…8,21e25 Similar trends were also seen in other tested antibiotics. 21e29 Compared to the study conducted by Jean et al, the only study investigated the susceptibilities to doripenem in Taiwan before our study, 15 we found that the MIC 90 s of doripenem and meropenem in P. aeruginosa and A. baumannii were both increased (6 mg/mL and 6 mg/mL vs. 1 mg/ mL and 4 mg/mL, >32 mg/mL and >32 mg/mL vs. 16 mg/mL and 16 mg/mL, respectively). We could not compare the differences in susceptibility rates, because Jean et al did not report these rates in their study.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…8,21e25 Similar trends were also seen in other tested antibiotics. 21e29 Compared to the study conducted by Jean et al, the only study investigated the susceptibilities to doripenem in Taiwan before our study, 15 we found that the MIC 90 s of doripenem and meropenem in P. aeruginosa and A. baumannii were both increased (6 mg/mL and 6 mg/mL vs. 1 mg/ mL and 4 mg/mL, >32 mg/mL and >32 mg/mL vs. 16 mg/mL and 16 mg/mL, respectively). We could not compare the differences in susceptibility rates, because Jean et al did not report these rates in their study.…”
Section: Discussionmentioning
confidence: 97%
“…Before our investigation, there has only been one study in Taiwan, which reported the susceptibility and in vitro activity of doripenem against clinically important bacteria. 15 Since the bacterial isolates used in that study were collected in 2005, 15 there might have been significant changes in drug resistance during this time period. Therefore, we conducted the present study using more contemporary clinical isolates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vancomycin MICs have been shown to vary depending on the method of measurement. Conflicting data have been published on the ability of commercial automated susceptibility testing methods in comparison with that of the Etest to provide accurate vancomycin MIC estimations for S. aureus [2][3][4]. In a recent study, Swenson et al [4] found that the BD Phoenix TM system (PMIC-102 and -104 cards with a vancomycin range of 0.5-16 g/mL) from Becton Dickinson (Sparks, MD) tended to categorise susceptible strains as vancomycin-intermediate S. aureus (VISA) and overall yielded higher MIC values compared with those obtained by the standard Etest.…”
Section: Differences In Vancomycin Minimum Inhibitory Concentrations mentioning
confidence: 99%
“…The nationwide Study for Monitoring Antimicrobial Resistance Trends (SMART) programme reported in 2005 that ertapenem was highly active against Enterobacteriaceae isolates [2]. Recently, however, ertapenem-resistant Enterobacteriaceae isolates have been reported in the UK [3] and have also been observed in Taiwan.…”
mentioning
confidence: 99%